Epidemiological trends and sex disparities in stroke disability-adjusted life years and mortality in Middle East and North Africa (MENA) - Ibrahim Khalil; Mohamed Wagdy; Ghassan Adnan Hashim; Hasan Naeem Kareem; Asma Alshanqiti; Md. Imran Hossain; Nabila Nur; Mst. Mahmuda Akter; Amal Abdi Ali; Sajjad Ghanim Al-Badri; Atef Akoum (Medicine, 2026)
Stroke remains a leading cause of disability and mortality globally, with pronounced burdens in the Middle East and North Africa (MENA) due to demographic shifts, conflict, and varying healthcare access. This study analyzes temporal trends and sex disparities in stroke-related disability-adjusted life years (DALYs) and deaths across MENA from 1990 to 2023, using Global Burden of Disease 2023 data, and extends projections to 2050 using Seasonal Autoregressive Integrated Moving Average (SARIMA) modeling. Age-standardized rates of stroke DALYs and deaths were extracted for the MENA region and 21 constituent countries, stratified by sex (International Classification of Diseases, 10th Revision: I60–I69). Temporal trends were assessed via estimated annual percentage changes using linear regression on log-transformed rates, with 95% confidence intervals (CIs). SARIMA models were fitted to regional time-series (both sexes) to forecast age-standardized rates through 2050, with 95% prediction intervals constrained to nonnegative values. Regionally, stroke DALYs declined with an estimated annual percentage change of –2.595 (95% CI:–2.641 to –2.549), steeper in females (–2.697; 95% CI:–2.758 to –2.636) than males (–2.487; 95% CI:–2.537 to –2.438). Deaths declined by –2.51 (95% CI:–2.556 to –2.464) overall. Qatar showed the fastest DALY decline (–4.437; 95% CI:–4.859 to –4.014), Libya the slowest (–1.087; 95% CI:–1.205 to –0.97). SARIMA forecasts project a 78.8% reduction in DALYs (from 1895 to 401 per 100,000) and 83.6% in mortality (94 to 15 per 100,000) by 2050, with lower 95% CIs reaching zero by 2043 due to long-term uncertainty. Declining stroke burdens in MENA reflect progress in risk factor control and acute care, with females showing steeper gains in most countries. Forecasts indicate near-elimination of stroke mortality and substantial disability reduction by mid-century, yet persistent sex and country disparities underscore the need for equitable, sustained interventions in prevention, acute management, and rehabilitation across vulnerable MENA settings.